Composite polysaccharide fibers prepared by electrospinning and coating - Maeda, N. (2013)
Composite polysaccharide fibers composed two oppositely charged natural polysaccharides, chitosan and hyaluronic acid, were prepared by electrospinning and subsequent coating The fiber size distribution was characterized by scanning electron microscopy. Chitosan/hyaluronic acid composite fibers were stable in water but showed controlled release of hyaluronic acid into phosphate buffered saline, and the presence of 3-wt% hyaluronic acid coating improved the swelling ratio to 30%. The resulting composite polysaccharide fibers have a number of potential biomedical applications in wound healing applications and in drug delivery systems.